2015
DOI: 10.1016/j.physbeh.2014.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sugar solutions on hypothalamic appetite regulation

Abstract: There are multiple hypotheses for the causes of the obesity epidemic. One such hypothesis is that dietary intake patterns have significantly shifted to include unprecedented amounts of refined sugar. We set out to determine some the unique metabolic changes that occur with initial exposure to dilute glucose, sucrose, high fructose corn syrup, or fructose solutions. Rats were given access to food, water and a sugar solution for 24 h, after which blood and tissues were collected. Fructose access (as opposed to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 77 publications
2
12
2
Order By: Relevance
“…This initial responses to sugar solutions are not the result from excess energy intake, as total caloric intake did not significantly differ among all five groups (Table 2). We also examined NPY and AgRP and failed to detect any significant differences (data not shown), which was consistent with our recent report [12].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This initial responses to sugar solutions are not the result from excess energy intake, as total caloric intake did not significantly differ among all five groups (Table 2). We also examined NPY and AgRP and failed to detect any significant differences (data not shown), which was consistent with our recent report [12].…”
Section: Discussionsupporting
confidence: 92%
“…These observations support the view that hypothalamic CCK plays an important role in energy control. We recently reported that 24 hour access to glucose solutions upregulated CCK expression whereas access to fructose resulted in significant downregulation of CCK [12]. In the current study, we replicated our finding that fructose access down-regulated CCK and can now report that this suppression takes place mainly in the PVN, not in the VMH or the LH.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations